HCV genotypes in haemodialysis units: a preliminary study - Hamzah, Hairul Aini; Mustafa Mahmoud, Mohammed Imad Al-Deen; Abdullah, Nasuruddin (2008)
Introduction: Serological verification among haemodialysis patients in Kuantan, Pahang, an East Coast town in Peninsular Malaysia is routinely updated for every 3 months by Ministry of Health. However, the determination of the HCV genotypes for each infected patient has not yet been attempted. This study aims at the determination of HCV genotypes among infected haemodialysis patients. Methodology: 22 seropositive patients out of 208 (10.5%) from 4 heamodialysis units (HDUs) were enrolled in this study during the period from March to August 2007. Detection of HCV RNA from serum was done by using RT-PCR technique targeting 212 bp of the 5’UTR region. Meanwhile, the base sequences of the above regions were deduced using the same primers as for the RT-PCR. The nucleotide sequences data were analyzed with Bioedit software and classification of the genotypes was done using neighbor-joining method together with known sequences obtained from NCBI homepage. Result: Out of 21 samples (male = 57%), 2 are negatives. The 19 positive HCV-RNA samples were subjected for sequencing analysis. The analysis showed that 63.2% (12/19) were of genotype 3, 26.3% (5/19) of genotype 1 followed by 5.3% (1/19) of genotype 4 and 1 isolate (5.3%) is undetermined. Furthermore, the genotype distribution showed discrete clustering among units. Sequence comparisons revealed that 4 strains from one HDU have a G insertion (-208) which is not detected in other strains including ones that were retrieved from NCBI sequence database. Conclusion: Genotype 3 is the most prevalent genotype found among heamodialysis patients in Kuantan which is in concordance with previously published HCV genotype prevalence in Malaysia. Furthermore, genotype clustering suggests a nosocomial and blood transfusion infection which requires further subtyping test. Meanwhile, nucleotide sequence analysis suggested that HCV adaptation to certain environment may lead to mutations in the well conserved region (5’UTR).